Stimulating myelin restoration with BDNF: a promising therapeutic approach for Alzheimer's disease - Zota, Ioanna; Chanoumidou, Konstantina; Gravanis, Achille; Charalampopoulos, Ioannis (Frontiers in Cellular Neuroscience, 2024)
Alzheimer's Disease (AD) is a chronic neurodegenerative disorder constituting the most common form of dementia (60-70% of cases). Although AD presents majorly a neurodegenerative pathology, recent clinical evidence highlights myelin impairment as a key factor in disease pathogenesis. The lack of preventive or restorative treatment is emphasizing the need to develop novel therapeutic approaches targeting to the causes of the disease. Recent studies in animals and patients have highlighted the loss of myelination of the neuronal axons as an extremely aggravating factor in AD, in addition to the formation of amyloid plaques and neurofibrillary tangles that are to date the main pathological hallmarks of the disease. Myelin breakdown represents an early stage event in AD. However, it is still unclear whether myelin loss is attributed only to exogenous factors like inflammatory processes of the tissue or to impaired oligodendrogenesis as well. Neurotrophic factors are well established protective molecules under many pathological conditions of the neural tissue, contributing also to proper myelination. Due to their inability to be used as drugs, many research efforts are focused on substituting neurotrophic activity with small molecules. Our research team has recently developed novel micromolecular synthetic neurotrophin mimetics (MNTs), selectively acting on neurotrophin receptors, and thus offering a unique opportunity for innovative therapies against neurodegenerative diseases. These small sized, lipophilic molecules address the underlying biological effect of these diseases (neuroprotective action), but also they exert significant neurogenic actions inducing neuronal replacement of the disease areas. One of the significant neurotrophin molecules in the Central Nervous System is Brain-Derived-Neurotrophin-Factor (BDNF). BDNF is a neurotrophin that not only supports neuroprotection and adult neurogenesis, but also mediates pro-myelinating effects in the CNS. BDNF binds with high-affinity on the TrkB neurotrophin receptor and enhances myelination by increasing the density of oligodendrocyte progenitor cells (OPCs) and playing an important role in CNS myelination. Conclusively, in the present review, we discuss the myelin pathophysiology in Alzheimer’s Diseases, as well as the role of neurotrophins, and specifically BDNF, in myelin maintenance and restoration, revealing its valuable therapeutic potential against AD.